ABO incompatible transplantation - Venera Altynova; Nazym Nigmatullina; Saltanat Rakhimzhanova; Nagima Mustapaeva; Samat Isakov (National Scientific Medical Center, 2017)
At present, the problem of the lack of donor organs for transplantation remains. The kidney transplantation from incompatibile donors exists with great caution and distrust. But it could significantly shorten the waiting time for the recipient of the donor organ. Incompatibility of the donor and recipient in the ABO system for decades was considered an absolute contraindication to organ transplantation due to the inevitable development of hyperactive rejection. Against the backdrop of a global body deficiency from cadaver donors, the development of lifelong donation is an alternative resource. According to the centers of transplantation in Japan, 45% of organ transplants are transplants with incompatibility according to the ABO system (nAVO). Successful overcoming of this barrier can help to expand the number of donors and, consequently, donor bodies. In addition, the introduction of ABO-incompatible organs into the practice of transplantation can shorten the waiting period.